Can we safely deform a plate to fit every bone? population-based fit assessment and finite element deformation of a distal tibial plate - Harith, Hazreen Haizi; Schmutz, Beat; Malekani, Javad; Schuetz, Michael A.; Yarlagadda, Prasad K. (Medical Engineering & Physics, 2016)
Anatomically precontoured plates are commonly used to treat periarticular fractures. A well-fitting plate can be used as a tool for anatomical reduction of the fractured bone. Recent studies highlighted that some plates fit poorly for many patients due to considerable shape variations between bones of the same anatomical site. While it is impossible to design one shape that fits all, it is also burdensome for the manufacturers and hospitals to produce, store and manage multiple plate shapes without the certainty of utilization by a patient population.